1975
DOI: 10.1159/000123631
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Organization of the Binocular Input to Frog Optic Tectum

Abstract: Single-unit recordings in the frog''s optic tectum have demonstrated the existence of a systematic spatial separation between the direct contralateral and indirect ipsilateral excitatory receptive fields. Marked differences in this spatial organization were found between paralyzed and anesthesized animals.Significant latency differences were found between sustained (class I/II) and transient (class III) contralateral fibers. Corresponding latency differences were also seen in ipsilaterally driven responses. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1977
1977
1995
1995

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
(12 reference statements)
1
0
0
Order By: Relevance
“…contribute to the difference in plasticity? We have determined that the intertectal delay in Xenopus is about 10 ms (Scherer & Udin, 1991), while the delay in Rana has been reported to be substantially longer, 20-45 ms (Gaze & Jacobson, 1963;Raybourn, 1975). In this paper, we have compared the two species using identical stimuli and have confirmed that the delay in Rana is several times longer than that in Xenopus.…”
Section: Introductionsupporting
confidence: 59%
“…contribute to the difference in plasticity? We have determined that the intertectal delay in Xenopus is about 10 ms (Scherer & Udin, 1991), while the delay in Rana has been reported to be substantially longer, 20-45 ms (Gaze & Jacobson, 1963;Raybourn, 1975). In this paper, we have compared the two species using identical stimuli and have confirmed that the delay in Rana is several times longer than that in Xenopus.…”
Section: Introductionsupporting
confidence: 59%